The 2014 autochthonous dengue fever outbreak in Tokyo: A case series study and assessment of the causes and preventive measures. (2020) - Kori, Mayuko; Awano, Nobuyasu; Inomata, Minoru; Kuse, Naoyuki; Tone, Mari; Yoshimura, Hanako; Jo, Tatsunori; Takada, Kohei; Tanaka, Atsuko; Mawatari, Momoko; Ueda, Akihiro; Izumo, Takehiro
Abstract: Objective: In 2014, an autochthonous dengue fever outbreak occurred around the Yoyogi Park in Japan for the first time in 70 years. Despite no local cases reported since then, the risk of another outbreak remains high. This study reviews the autochthonous dengue fever cases of the outbreak, investigates its causes, and delineates preventive measures against autochthonous dengue epidemics. Methods: We conducted a case series study of 15 patients who visited our institution during the 2014 outbreak. We collected and evaluated data on the surveillance of vector mosquitoes, weather, pest control, travelers' origins and destinations, and imported dengue fever cases using reports made by public institutions. Results: All patients recovered with supportive treatments and none met the diagnostic criteria for severe dengue infection. Twelve patients with positive real-time polymerase chain reactions were confirmed as having dengue virus-1 infections. We found no obvious associations between the number of mosquitoes and the weather, or between the number of imported dengue fever cases and that of travelers. Insect growth regulator (IGR) against vector mosquitoes has been used since 2014 for pest control, but the number of larvae has not declined in the Yoyogi Park, although that of imagoes has been relatively suppressed. Conclusion: The 2014 outbreak emerged without particularly favorable climate conditions for vector mosquitoes. We found no obvious associations between the number of travelers or the imported dengue fever cases and the outbreak, but the increasing number of travelers may contribute to another outbreak. Pest control, including IGR, remains essential for infection control. Highlights: We studied 15 patients with autochthonous dengue fever during a local outbreak. This outbreak emerged without favorable climate conditions for mosquitoes. There were no increased number of travelers or imported dengue cases. Pest control using insect growth regulator can be effective for infection control.